Sports Promotion in the Western Canadian City: The Example of Early Edmonton - Betke, Carl (Urban History Review / Revue d'histoire urbaine, 1983)
Edmonton's rapid growth in the early 1900s was accompanied by an equally rapid growth in both professional and amateur sports. This paper explores the objectives of the city's sports promoter. In the main, Edmonton's boosters implemented recreation and entertainment plans similar to ones established elsewhere by agencies such as the Young Men's Christian Association, the American National Baseball Commission and international sports news services. These programmes, neither distinctive nor unusually exploitative, were put in place by local entrepreneurs with a minimum amount of contention.